Islamic social reporting on value of the firm: Evidence from Indonesia Sharia Stock Index - M. Jihadi; Elok Vilantika; Bambang Widagdo; Fatmawati Sholichah; Yanuar Bachtiar (Cogent Business & Management, 2021)
The purpose of this study is to examine and analyze the intervening effect of Islamic Social Responsibility and capital structure on the relationship between profitability and firm value. This research is an explanatory research with a quantitative descriptive approach. The data used were obtained from annual reports of sampled firm as published on the Indonesia Stock Exchange (IDX) for the 2013-2018 period. 39 companies classified as basic and chemical industries and listed in the Indonesia Sharia Stock Index (ISSI) were sampled using the purposive sampling technique. The data were analyzed using Structural Equation Model (SEM) and Sobel test to analyze the indirect effect. The results show that profitability, ISR and capital structure have a positive significant effect on firm value. Profitability was found to have positive affect on ISR and negative affected the capital structure. A mediation test showed that ISR and capital structure does not mediate the effect of profitability on firm value.
Keywords: 650; capital structure; Islamic social reporting; profitability; sharia stock; value ofthe firm